Adversaries of dance : from the Puritans to the present - Wagner, Ann Louise (Urbana : University of Illinois Press, 1997)
Whether in the private parlor, public hall, commercial "dance palace," or sleazy dive, dance has long been opposed by those who viewed it as immoral - more precisely as being a danger to the purity of those who practiced it, particularly women. In Adversaries of Dance, Ann Wagner presents a major study of opposition to dance over a period of four centuries in what is now the United States.
1. The Pre-Reformation Tradition -- 2. The Voices of Protestant Reformers -- 3. The Puritans in New England: The Seventeenth Century -- 4. The Gentry and the Awakening: The Eighteenth Century -- 5. Early Evangelicals and American Etiquette: 1800-1839 -- 6. The Evangelical Mainstream and Radical Reformers: 1840-60 -- 7. Conservatives, Liberals, and the City: 1865-89 -- 8. Embattled Fundamentalists and the Rhetoric of Moral Panic: 1890-1929 -- 9. Urban Reformers and the Dance Hall: 1908-40 -- 10. The Polemic Upstaged: 1930-69 and Beyond -- 11. The Nature of Dance and the Polemic in Reprise -- 12. Aesthetics, Morality, and Gender -- App. A. Bible Verses on Dance -- App. B. Known European Adversaries of Dance
Includes bibliographical references and index.
Keywords: Dance -- Moral and ethical aspects -- United States -- History; Dance -- Social aspects -- United States -- History; United States -- Moral conditions; Dance -- Moral and ethical aspects; Dance -- Social aspects; Moral conditions; United States; History